A study on employee training and development in Hyundai organisation – Chennai - CHERUKUR, MR. RAM BABU; PRIYA.K, MS. MOHANA (The journal of contemporary issues in business and government, 2020)
Training and development makes employees more productive. Training and development are becoming big business nowadays and more important for any organization that wants to take advantage of changes, techniques and improvements. The existing workforce is trained to increase their productivity, newly joined employees will also be trained and motivated to contribute their best towards the organization. The employees will be more confident about themselves and passionate about their job. They will adapt to technological changes and innovations more readily. Training and development need assessments, training design and delivery and transfer of training. Growing business environment needs new ideas like updated and strategic training and development to make business grow fast as well , we need to adapt ourselves for the future business environment, making our employees updated will give the best result for the organization. Nowadays many organizations are spending much to train their employees and make them updated. The training program has to be designed perfectly for the employees to achieve long and short term goals of the organization and employees as well. After the training and development program every employee has to be evaluated by their performance and should get their feedback.